GAYA BAHASA DAN STRATEGI BELAJAR BAHASA SISWA MI AL KIFAYAH - Nursalim; Rozi Siregar; Anusirwan Hamidi Harahap (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language style and learning strategies play an important role in the success of language learning at the elementary level. Students have different language styles that influence how they receive, process, and express language. This article aims to analyze language styles and language learning strategies used by students at MI Al Kifayah. The method used is a literature study by reviewing relevant theories and previous research. The results show that appropriate learning strategies combined with an understanding of students’ language styles can improve language skills, including speaking, reading, writing, and listening. Therefore, teachers need to apply adaptive and varied strategies to support optimal language learning outcomes.